Contextualizing Canines, a Dog Burial, and Enslaved Life on a Virginia Plantation. (1st September 2016) - Greer, Matthew C.
Abstract : In the early nineteenth century, members of one household of the enslaved community at Virginia's Montpelier plantation buried their dog near the duplex they called home. This action, on its own, unfortunately does not speak directly to the broader experiences of Africans or their descendants forced into American bondage, or the specific experiences of the women and men enslaved at Montpelier. However, by contextualizing dogs in the African Atlantic and the specific landscapes of Montpelier, such narratives come into focus, allowing us to explore the roles the animal may have played in the daily life of an enslaved household.